2013
DOI: 10.9775/kvfd.2013.8776
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Local Application of 1% Tioconazole in the Treatment of Bovine Dermatophytosis

Abstract: SummaryThis study consisted of twenty-five dermatophytotic cattle, aged 1.5-11 months obtained from Kars province and its surrounding, diagnosed as dermatophytosis following clinical and microbiologically. All animals were divided into two groups; trial group (n=15) and control group (n=10). The skin lesions of the trial animals were treated using a pomade containing 1% tioconazole once daily for a period of 5 days. In 12 of the trial animals the amount of keratinized tissue found in the dermatophytosis lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Bovine dermatophytosis is an important skin disease that has an economic significance and important public health considerations for cattle and farmers. Trichophyton verrucosum is the most common isolate from cattle with dermatophytosis and was most frequently isolated from cattle in this report . Various medical and vaccine treatment options exist for the management of bovine dermatophytosis with varying practical and economic considerations .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Bovine dermatophytosis is an important skin disease that has an economic significance and important public health considerations for cattle and farmers. Trichophyton verrucosum is the most common isolate from cattle with dermatophytosis and was most frequently isolated from cattle in this report . Various medical and vaccine treatment options exist for the management of bovine dermatophytosis with varying practical and economic considerations .…”
Section: Discussionmentioning
confidence: 89%
“…Dermatophytosis is an important zoonotic disease of humans and animals . In cattle, dermatophytosis is most frequently caused by Trichophyton verrucosum . Clinical lesions are characterized by nonpruritic, multifocal lesions of alopecia with scale .…”
Section: Introductionmentioning
confidence: 99%
“…Medication cannot penetrate the crusts; the crusts should be removed by scraping or brushing. Lesion should be treated at least twice, three to five days apart (15,16,24). In present study, crusts were removed by scraping, later silver nitrate pencil application was made only for once.…”
Section: Resultsmentioning
confidence: 99%
“…Systemic applications are including; ivermectin, ethylenediamine dihydriodide orally, griseofulvine orally (11,12,14). Topical applications are including; thiabendazole was made in glycerine, tincture of iodine, 1% tioconazole, 10% enilconazole, propolis ointment, Whitfield's ointment, propolis and Whitfield's ointment, miconazole ointments, garlic solution, zinc oxide, salicylic acid + benzoic acid + sulfur + iodine and vaseline combination (4,5,15,16,17,18,19,20). Topical applications should be made 3-4 times.…”
Section: Introductionmentioning
confidence: 99%
“…Ponugoti, (2018) reported this finding suggested that henna extract may be used as an alternative source of antifungal agent for the protection of fungal infection. Başoğlu et al, (1998), Kırmızıgül et al (2008aKırmızıgül et al ( , 2009bKırmızıgül et al ( , 2013c, Cam et al, (2009) repoted that systemic antifungal and topical treatment were used for the treatment of wounds caused by dermatophytes. In a study has done with henna by Muhammed H and Muhammed S, (2005) reported that the mixture of powder henna leaves with water prevents the wound from growing in burns.…”
Section: Introductionmentioning
confidence: 99%